Yoga: An Exploration of Its Cultural Adaptation and Practice in Japan - M Kamraju; Devkar Bhausaheb Sonaji (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2023)
This research paper aims to explore the cultural adaptation and practice of yoga in Japan. It investigates the historical development of yoga in Japan, examining how it was introduced and integrated into Japanese culture. The paper also delves into the cultural influences that shaped the adoption and evolution of yoga in the country, both from traditional and modern perspectives. Furthermore, it examines the role of yoga in Japanese religious and spiritual traditions, highlighting the syntheses between yoga and Zen Buddhism. The study also explores the incorporation of yoga as a form of physical exercise in Japanese society, examining its impact on health, fitness, and body culture. Additionally, it investigates the connection between yoga and Japanese martial arts, analyzing the integration of mind-body practices. The paper further investigates the integration of yoga in Japanese education, exploring its inclusion in school curricula and its effects on students. It also examines yoga retreats and centers in Japan, analyzing them as spaces for spiritual growth and personal transformation. Moreover, the research paper explores the different styles and methods of yoga practiced in Japan, examining adaptations, innovations, and variations. Finally, it discusses the social and cultural impacts of yoga on Japanese society, including community building, wellness movements, and lifestyle trends. Through this comprehensive exploration, the paper provides valuable insights into the cultural adaptation and practice of yoga in Japan, shedding light on its unique manifestation in the country's rich cultural tapestry.